(3TQM GdTGWHjIs - (3GHi TGeg YHO GdQMef Hf ESeGYjd GdOeTbjs; (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3jHOC HChd ShQI Bd YeQGf s
(3BNQgG (B:s
(3hbGd GdTGYQ (B: (3jGHGHi CfJ hahc GdCTfH cCfeG PQ Ydjg GdRQfH ChRfLHjd hgh YfOi CWjH hGdRQfH hGdbQfad Ohf BNQ EHQGR GdeYGfi GdeNJUQ s
(3SeYJ Ydi GdeDda hYdjgG NWg HUMI GdSeGYs
(3cJHJ ai MjGI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
Keywords: (3GdbQGAGJ hGdJLhjOs